1991
DOI: 10.1128/jb.173.8.2435-2441.1991
|View full text |Cite
|
Sign up to set email alerts
|

Amplification and deletion of a nod-nif region in the symbiotic plasmid of Rhizobium phaseoli

Abstract: One remarkable characteristic of the genomes of some Rhizobium species is the frequent occurrence of rearrangements. In some instances these rearrangements alter the symbiotic properties of the strains. However, no detailed molecular mechanisms have been proposed for the generation of these rearrangements. To understand the mechanisms involved in the formation of rearrangements in the genome of Rhizobium phaseoli, we have designed a system which allows the positive selection for amplification and deletion even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
73
0
1

Year Published

1991
1991
2000
2000

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 46 publications
6
73
0
1
Order By: Relevance
“…The event was a deletion in the pSym of about 120 kb that occurs with a cumulative frequency of 1.7 x 10-2 and was recA dependent. This rearrangement was similar to others previously found in our laboratory (37).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The event was a deletion in the pSym of about 120 kb that occurs with a cumulative frequency of 1.7 x 10-2 and was recA dependent. This rearrangement was similar to others previously found in our laboratory (37).…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, a high frequency of rearrangements has been found to be associated with the presence of repeated DNA (12, 38). Genomic instability and rearrangements that affect nodulation or nitrogen fixation abilities have been observed in several Rhizobium species (25,27,37,42).…”
mentioning
confidence: 99%
“…In general, strains within the Rhizobium genus are fast growing, such as there studied here that nodulate beans. They appear to be more taxonomically diverse and ecologically adaptable than the slower growing strains from other genera like Bradyrhizobium and Azorhizobium These differences probable occur because in the slow growing strains the genetic information, in general, is contained in the chromossomal DNA, while in fast growing strains many genes, including those related to biological nitrogen fixation are located on plasmids which confers dynamic qualities to the genome (5,12). These characteristics favor recombination between genotypes of the Rhizobium population present in soils (14).…”
Section: Resultsmentioning
confidence: 99%
“…PCA also verified that the R. leguminosarum bv. phaseoli strains had more variation among themselves than the R. tropici did, probably due to the formers higher genetic plasticity (12,13). In addition, this analysis identified adequate primers for strain identification.…”
Section: Resultsmentioning
confidence: 99%
“…As deletions in symbiotic plasmids are common (Romero et al, 1991), we consider it most likely that the Rm220-3 mos locus is the result of a deletion. Consistent with this suggestion a recent survey of the frequency of inositol rhizopines has shown that only one strain (Rm220-30) out of 22 rhizopine strains isolated produced SI (Wexler e t al., 1995).…”
Section: Evolution Of Rhizopine Genesmentioning
confidence: 99%